2008
DOI: 10.1614/wt-07-093.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed Infestation in Turmeric in Okinawa, Japan

Abstract: A field experiment was conducted in Okinawa, Japan from 2005 to 2007 to evaluate the effect of purple nutsedge and other weeds on turmeric growth and yield and determine the effective weed-control period to minimize crop interference. Treatments consisted of all weeds removed at 70, 115, and 160 d sequentially after planting (DAP), all weeds except purple nutsedge removed at these three dates, plus weedy and weed-free controls. Purple nutsedge density increased until 115 DAP when grown alone with turmeric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The lowest rhizome yield per plant (128.01 g), yield per plot (2.76 kg) and yield per hectare (5175.03 kg) were recorded in fallow plots. Similar results were supported by the findings of [3] in ginger who opined that mulches were useful in altering hydrothermal regime of the soil and provide favorable environment for rhizome development. Earlier report [7] in ginger also showed that application of mulch might have checked the weed growth, reduced the evapotranspiration losses which provide congenial condition for better penetration, proliferation and ramification of roots thereby increased the yield.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The lowest rhizome yield per plant (128.01 g), yield per plot (2.76 kg) and yield per hectare (5175.03 kg) were recorded in fallow plots. Similar results were supported by the findings of [3] in ginger who opined that mulches were useful in altering hydrothermal regime of the soil and provide favorable environment for rhizome development. Earlier report [7] in ginger also showed that application of mulch might have checked the weed growth, reduced the evapotranspiration losses which provide congenial condition for better penetration, proliferation and ramification of roots thereby increased the yield.…”
Section: Discussionsupporting
confidence: 83%
“…In Tamil Nadu the major pest in turmeric is shoot borer caused by Dichocroces punctiferalis and the major disease is rhizome rot caused by Pythium graminicolum. Crop loss due to weed is more than 40% [3] and pest and disease is 50-80% [4].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence pattern, growth and yield of turmeric plants, and weed growth in the field experiment suggested that turmeric planting should be done in April followed by March in Okinawa, Japan (Ishimine et al, 2004). Hossain et al (2008) reported that purple nut sedge (<3000 plants per m 2 ) did not significantly reduce turmeric yield, whereas the combined weed species reduced yield by as much as 40%. He suggested integrating biological weed management practices using rabbits, goats, sheep, ducks, cover crops, or intercrops to control weeds in turmeric fields.…”
Section: Weed Managementmentioning
confidence: 98%
“…The order of total weed dry weight was as follows: February planting > March planting > April planting > May planting > June planting. The investigation by Hossain et al (2008) indicated that for reducing weed interference, and obtain high yield, turmeric should be planted in a 30 cm triangular pattern, on tworow ridge spaced 75-100 cm apart. Hossain (2005) concluded that seed rhizomes weighing 30-40 g and/or mother rhizome could be planted in a 30 cm triangular pattern at a depth of 8-12 cm on two ridges spaced 75-100 cm apart from March to April in order to reduce weed infestation and obtain higher yield in Japan; besides, mulching also reduced weed growth and improved rhizome yield.…”
Section: Weed Managementmentioning
confidence: 99%